Analysis of Industrial Agglomeration and Economics Growth in 2013-2019 (Case: Six Provinces on Java Island) - Fitri Bahari; Zulfatun Nisa (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
This study aims to analyze degree of agglomeration industry in manufacture product between DKI Jakarta, West Java, Central Java, Yogyakarta, East Java, and Banten in 2013-2019. Degree of agglomeration industry was calculated by using Balassa Index and using panel data with fixed effect model analysis to explain determinants of economic growth in Province- Province Java Island. The results of this study show that degree of Agglomeration Industry West Java has mild agglomeration. Central Java, East Java and Banten has weak agglomeration. DKI Jakarta and Yogyakarta has no agglomeration industry in manufacture product. And the empirical results of determinants of economic growth indicate that Agglomeration has a positive influence. While Labor have a negative effect to Economic Growth. The results also suggest that investment has an un-significant influence on Economics growth.Keywords: Economic Growth, Agglomeration, Labor, Investment.